Aged for Mayhem (A Tuscan Vineyard Cozy Mystery-Book 3 - Fiona, Grace (Lukeman Literary, 2020)
"Very entertaining. I highly recommend this book to the permanent library of any reader that appreciates a very well written mystery, with some twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews, Roberto Mattos (regarding Murder in the Manor) AGED FOR MAYHEM (A TUSCAN VINEYARD COZY MYSTERY) is book #3 in a charming new cozy mystery series by #1 bestselling author Fiona Grace, author of Murder in the Manor (Book #1), a #1 Bestseller with over 100 five-star reviews-and a free download! Olivia Glass, 34, turns her back on her life as a high-powered executive in Chicago and relocates to Tuscany, determined to start a new, simpler life-and to grow her own vineyard. Olivia is thrilled to take her first trip to Florence, and that her love life is heating up. She is even more ecstatic that her small vineyard produces its first bottle of wine. Yet when a famous wine critic trashes her wine-and then ends up dead himself-Olivia finds herself in the crosshairs of a murder that she is pinned for-and that she must urgently solve herself. Is the Tuscan life really for Olivia? Or was it all just a fantasy? Hilarious, packed with travel, food, wine, twists and turns, romance and her newfound animal friend-and centering around a baffling small-town murder that Olivia must solve-AGED FOR MAYHEM is an un-putdownable cozy that will keep you laughing late into the night.
Keywords: Krimi, detektivky